Potensi Pengembangan Olahraga Rafting Di Sungai Kaliboyo Kecamatan Tulis Kabupaten Batang - Mukhammad Awwab; Sahri Sahri (Jurusan Pendidikan Kesehatan dan Rekreasi, 2023)
Background: Natural abilities are all the medicinal displays and medicinal assets defined in an area. Natural abilities can be processed and can be developed. The optimal development and utilization of the potential for Rafting Sports on the Kaliboyo River, Tulis District, Batang Regency, can increase economic growth and the welfare of the surrounding community. This study aims to determine the potential for the development of rafting on the Kaliboyo River, Tulis District, Batang Regency. Methods: This study uses a qualitative approach with data collection techniques of observation, interviews and documentation. As a step to obtain data, a number of parties were involved including the Batang Regency Youth and Sports Tourism Office (DISPARPORA), the local village head (Manager), as well as elements of the community or rafting actors in Batang district. Results: The results showed that the potential for the development of rafting sports on the Kaliboyo River, Tulis District, Batang Regency is classified as a promising potential to be developed into spot tourism, so that it can increase and increase human resources and economic growth, especially for the people in the Kaliboyo river environment, Tulis District, Batang Regency. Conclusions: There are two locations in Batang Regency that have potential and have been developed as rafting tours where these locations can be developed more broadly into an integrated tourist attraction. These locations include Kaliboyo River, Pandansari Rafting Village.